AB1017 Sleep Fragmentation and Biomarkers in Juvenile Idiopathic Arthritis. (9th June 2015) - Ward, T.; Voss, J.; Yuwen, W.; Foll, D.; Gohar, F.; Ringold, S.
Abstract : Background: Children with JIA have been shown to have increased frequency of sleep fragmentation when compared to healthy peers. The relationship between this fragmentation and the underlying inflammatory process has not been established. The proteins S100A12 and myeloid-related protein 8/14 (MRP8/14) are associated with disease activity in JIA and have also been associated with sleep disordered breathing in children and adults without JIA. The associations between the S100A12 and MRP8/14 proteins and sleep fragmentation have not been evaluated in children with JIA and the contribution of inflammation to sleep disturbance is not known. Objectives: To measure the associations between inflammatory S100A12 and MRP8/14 protein biomarkers and sleep fragmentation (wake after sleep onset) in 8-14 year-old children with polyarticular and extended oligoarticular juvenile idiopathic arthritis (JIA). Methods: Forty children between 8-to-14 years of age, with extended oligoarticular (n=15) and polyarticular (n=25) JIA and their parents participated in this cross-sectional, observational study. The treating rheumatologist assessed disease activity and inactive disease was measured using modified provisional ACR criteria for clinically inactive disease. Serum samples were obtained during each child's routine rheumatology clinic visit. Children completed the PedsQL™ Multidimensional Fatigue scale, daily sleep diaries, and wore actigraphy monitors for 9 consecutive days. Parents completed the Children's Sleep Habits Questionniare (CSHQ) regarding their child's sleep habits. Results: Of the 40 children, 22 (55%) had inactive disease. 68% scored above the CSHQ clinical cut-off score for sleep disturbances. Average sleep duration was 7.5 hours. Mean S100A12 and MRP8/14 protein levels were not significantly different between JIA categories or between children with active versus inactive disease. After controlling for age and joint count, wake after sleep onset was a significant predictor for S100A12 but not MRP8/14 proteins. Conclusions: Inadequate amounts of sleep, increased amounts of wake, and poor sleep quality were observed in our sample, regardless of whether children had active or inactive disease. Similarly, children with extended oligoarticular and polyarticular arthritis had similar levels of inflammatory proteins and sleep disruption. Additional prospective evaluation of these proteins in larger cohorts of children with more variation in disease activity is needed to better understand the associations between these biomarkers, inflammation, and sleep disturbances in JIA. Disclosure of Interest: None declared